Analysis and prevention of component and equipment failures - Miller, Brett A.; Shipley, Roch J.; Parrington, Ronald J.; Dennies, Daniel P. (ASM International, 2021)
"Provides information and insights on the factors that determine the useful service life of engineering components and the likely timing and mode of failure. It addresses nearly every stage of the product lifecycle from materials selection and design to manufacturing, operation, maintenance, and repair. It explains how to use life assessment methods to evaluate the effect of corrosion, fatigue, brittle fracture, elevated temperature, and other forms of damage. It also includes a section that examines the effects of casting, forming, welding, heat treating, and other manufacturing processes on component lifetime and performance. The final and by far largest section in the volume presents and analyzes the failure of metal shafts, fasteners, bearings, springs, and gears as well as pressure vessels, boilers, heat exchangers, pipelines, bridges, cranes, rail equipment, and medical devices."-- ASM Handbooks Online website, viewed on April 28, 2022.
"Volume 11A is intended to be used in conjunction with ASM handbook, volume 11, 'Failure analysis and prevention'"--Preface page, viewed online on April 28, 2022.
"Selected articles were published digital first in advance of the full volume release. The volume was prepared under the direction of the ASM International Handbook Committee."--Publication history page, viewed online on April 28, 2022.
Some online versions include index.
Includes glossary of terms.
Keywords: Metals -- Fracture -- Handbooks, manuals, etc.; Metals -- Analysis -- Handbooks, manuals, etc.; Machine parts -- Failures -- Handbooks, manuals, etc.; Machine parts -- Analysis -- Handbooks, manuals, etc.; Failure analysis (Engineering) -- Handbooks, manuals, etc.; elektronické knihy; electronic books